Border Area Management: How Should Indonesia Reform? - Darajati, Muhammad Rafi; Syafei, Muhammad; Sudagung, Adityo Darmawan (Uti Possidetis: Journal of International Law, 2023)
This article examines how state territorial regulation can encourage development in Indonesia's border regions. This article also tries to explain the need for better management of borders between countries because there are several obstacles in implementing cross-border regulations. This research uses qualitative methods by taking the perspective of international law and constitutional law and collecting data through field research and reviewing related literature. Field research was carried out for 3 months by conducting in-depth interviews with several informants. Secondary data was obtained from reviewing books, journals, writings and mass media regarding international law, international relations and constitutional law. This research shows that the idea of ​​reforming border management between countries must be based on several aspects, namely law, institutions, development approaches and spatial planning. Keywords: border area management; governance; state territory